State Pharmacopoeia of Ukraine and Pharmaceutical Law: State Quality Standard for Medicines for Standardization and Quality Control During Circulation in Healthcare and Pharmacy Sectors - Lavoshnik, Olena; Gryzodoub, Oleksandr; Diachenko, Lesia; Trunova, Anna; Kotova, Elina (SSP Modern Pharmacy and Medicine, 2025)
The organizational, legal, scientific, theoretical, expert, educational, methodological, and practical measures to support state standards for the quality, standardization, and control of medicines during their circulation in healthcare and pharmacy are comprehensively examined. The quality requirements for medicines are summarized, and the activities are systematically categorized into organizational-legal, scientific-theoretical, and practical areas. Proposals have been developed to enhance and increase the effectiveness of the quality management system, while the components of external quality assessment in professional testing programs are carefully studied. Additionally, the document outlines the directions for scientific-expert, normative activities, and international cooperation, and it explores collaborative agreements with scientific and regulatory institutions, paving the way for innovative practices that further improve public health outcomes and safety standards. Furthermore, the research emphasizes the importance of cross-disciplinary approaches, integrating modern technological solutions and data-driven strategies to streamline regulatory processes and ensure consistent adherence to safety protocols. Stakeholder engagement, including input from healthcare professionals, pharmacists, and researchers, is considered crucial for identifying emerging challenges and best practices within the quality control landscape. Strategic partnerships with international organizations reinforce a global commitment to quality assurance, enabling comprehensive knowledge exchange and harmonization of regulatory standards. These initiatives ultimately contribute to a robust framework that safeguards public health, fosters improvement in pharmaceutical governance, and enhances system resilience in the face of challenges.